In the company of strangers : family and narrative in Dickens, Conan Doyle, Joyce, and Proust - McCrea, Barry, 1974- (Modernist latitudes., 2011)
This title shows how a reconception of family and kinship underlies the revolutionary experiments of the modernist novel. While stories of marriage and long-lost relatives were a mainstay of classic Victorian fiction, the book suggests that rival countercurrents within these family plots set the stage for the formal innovations of Joyce and Proust. By investigating how the question of family is a hidden key to modernist structure and style, the book explores the formal narrative potential of queerness and in doing so rewrites the history of the modern novel.